Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s11136-008-9325-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual quality of life: adaptive conjoint analysis as an alternative for direct weighting?

Abstract: In the schedule for the evaluation of individual quality of life (SEIQoL) the weights for five individualized quality of life domains have been derived by judgment analysis and direct weighting (DW). We studied the feasibility and validity of adaptive conjoint analysis (ACA) as an alternative method to derive weights in 27 cancer patients and 20 patients with rheumatoid arthritis. Further, we assessed the convergence between direct weights and weights derived by ACA, and their correlation with global quality-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…There is some debate in the broader SEIQoL literature on validity, reliability, responsiveness and practicality [29] and limited critique of conceptual [26,28,30] and practical [11,15,16,24,31] aspects of the SEIQoL-DW. However, most papers citing the instrument are uncritical, reporting scores attained with little further comment.…”
mentioning
confidence: 99%
“…There is some debate in the broader SEIQoL literature on validity, reliability, responsiveness and practicality [29] and limited critique of conceptual [26,28,30] and practical [11,15,16,24,31] aspects of the SEIQoL-DW. However, most papers citing the instrument are uncritical, reporting scores attained with little further comment.…”
mentioning
confidence: 99%
“…Still, one‐fifth (7/32, 22%) of participants chose the dominated combination, a higher proportion than Stiggelbout et al. 22 (4/45, 9%) found. A likely explanation for the disparity is Stiggelbout et al.…”
Section: Discussionmentioning
confidence: 63%
“…One study looked at the external validity of ACA‐derived utilities by assessing their consistency with preferences for medication profiles in HIV patients 21 . The other study compared weights for individualized quality of life domains derived from direct weighting vs. ACA, in rheumatology and cancer patients 22 . The latter study additionally assessed ACA completion, response consistency, and compensatory decision making (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This variability has been associated with the degree of participation (major or minor), 34,38 sex, education, living conditions, occupational status, 39 health literacy, 40 and the impact of the "sick role." 41 Critical care nurses should assess each patient to determine the level and role of decision making the patient prefers. Various assessment tools can be used, such as the Control Preference Scale, 42 the Autonomy Preference Index, 43 and the Health Opinion Survey.…”
Section: Participation In Decision Makingmentioning
confidence: 99%
“…Various assessment tools can be used, such as the Control Preference Scale, 42 the Autonomy Preference Index, 43 and the Health Opinion Survey. 44 Stiggelbout et al 41 have suggested a simple and quick way to assess a patient for the patient's preferences regarding information and participation in medical decisions. Two questions can be asked: (1) Would you always want to be fully informed about the benefits and risks of medical treatment?…”
Section: Participation In Decision Makingmentioning
confidence: 99%